Agility in a small software firm: a sense-and-respond analysis. (1st December 2008) - Schmidt, Thomas; Mathiassen, Lars
Small software firms are vulnerable to environmental uncertainty. While agile methods and other technologies offer suggestions to this challenge, we know little about how these firms combine project and firm level capabilities to effectively respond to changes. On this backdrop, we examine a small Danish software firm, TeachTech Inc., through the lens of Haeckel's sense-and-respond approach. Our analysis suggests that: the firm has appropriate sense-and-respond cycles, but improving process modularity and human resource flexibility, could increase its ability to respond faster and more effectively; the firm focuses on specific business goals, but these are not clearly explicated and expressed as empowering governing values enabling a quick and coordinated response; complex and demanding challenges are related to dynamically reassigning commitments and the supporting mechanisms are insufficient; a modularised product portfolio leverage some of the impeding restrictions. The article concludes with a discussion of the implications of these findings for theory and practice.